Determinación de ecuaciones alométricas para estimar biomasa y carbono en Pinus patula Schl. et Cham - Díaz Franco, Rosalino; Acosta Mireles, Miguel; Carrillo Anzures, Fernando; Buendía Rodríguez, Enrique; Flores Ayala, Eulogio; Etchevers Barra, Jorge D. (CATIE, Turrialba (Costa Rica), 2015)
11 páginas: 3 tablas